1 Del. Rev. Stat. 215-216 (1852) - (:unkn) unknown (My University, 1852)
Title Tenth-Of Corporations, Chapter 73-Of the city of Wilmington, § 27: Authorized the city council to regulate the storage of gunpowder.
Keywords: GUNPOWDER - STORAGE